(untitled) (UNED Research Journal, 2021)
Introduction: Cucumber is among Costa Rica’s main vegetable crop, and selection criteria for yield are best studied by path coefficient analysis, which divides correlation coefficients into direct and indirect effect components. Objective: To obtain a path analysis for greenhouse cucumber yield. Methods: The crop was planted on coconut fiber as substrate, and managed with fertigation, from January to May 2015. Seven variables were evaluated. Results: Yield showed a positive and highly significant correlation with number of fruits per plant (r=0,39**). The main positive direct effects on yield were exhibited by number of fruits per plant (path coefficient-PC=1,75), fruit weight (PC=1,44), fruit diameter (PC=0,17) and fruit length (PC=0,06), while maximum positive indirect effects on yield were exhibited by fruit length (PC=1,31), fruit diameter (PC=0,95) and percentage of total soluble solids (PC=0,89) through fruit weight. On the other hand, the only negative direct effect on yield was exhibited by percentage of total soluble solids (PC=-0,01). Conclusions: Under these conditions, number of fruits per plant and fruit weight were the main yield contributing variables.